2007
DOI: 10.1007/s11461-007-0025-0
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological effects of forest litter and soil in the Simianshan Mountains in Chonging, China

Abstract: A preliminary study of the hydrological effects of forest litter and soils in the Simianshan Mountains was carried out. Results indicate that the annual accumulation of different forest litters is about 6.80-20.21 t/hm 2 and the maximum water carrying capacity ranges from 1.8 to 4.6 mm. Among them the water carrying abilities of the litter of Lithocarpus glabra and natural deciduous forests are larger than that of Pinus massoniana. A power function relationship exists between the accumulated water-carrying vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Previous studies into the effects of the litter layer on runoff and water balance have been limited to individual hydrological processes; for example, by examining the water-holding capacity of the litter layer in order to estimate the factors that control litter interception (Sato et al 2004;Rao and Zhu 2007;Zhang et al 2009;Li et al 2013). Continuous field measurements of litter interception can only be obtained using a sheet-shaped weighing lysimeter (Schaap and Bouten 1997;Gerrits et al 2007Gerrits et al , 2010 or a permeable basin with a tipping bucket rain gauge to continuously monitor the water that drains from the litter layer into the soil (Bulcock and Jewitt 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies into the effects of the litter layer on runoff and water balance have been limited to individual hydrological processes; for example, by examining the water-holding capacity of the litter layer in order to estimate the factors that control litter interception (Sato et al 2004;Rao and Zhu 2007;Zhang et al 2009;Li et al 2013). Continuous field measurements of litter interception can only be obtained using a sheet-shaped weighing lysimeter (Schaap and Bouten 1997;Gerrits et al 2007Gerrits et al , 2010 or a permeable basin with a tipping bucket rain gauge to continuously monitor the water that drains from the litter layer into the soil (Bulcock and Jewitt 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The maximum water-holding capacity of the forest litter layer in high-elevation karst areas was found to be lower than that found in this study. Rao and Zhu (2007) studied the water-holding characteristics of evergreen broadleaved forest in a middle subtropical monsoon climate zone. The litter layer thickness for different forest types was 2.2-3.0 cm, the storage volume was 6.80-20.21 t/ha, the maximum waterholding capacity was 18.24-46.37 t/ha, and the maximum water-holding rate was 284-477%.…”
Section: Discussionmentioning
confidence: 99%
“…The water regulating function of litter and moss will increase with the Abies fabric forest succession. Rao and Bi (2005) concluded that the effective maximum water holding capacity of forest litter in the Simian Mountain in Sichuan Province was between 1.8 and 4.6 mm. It is well accepted that roots stop rill development while the litter layer, limits splash erosion.…”
Section: Litter Factormentioning
confidence: 99%